Plant Growth and Drought Tolerance-Promoting Bacterium for Bioremediation of Paraquat Pesticide Residues in Agriculture Soils - Inthama, Phatcharida; Pumas, Pamon; Pekkoh, Jeeraporn; Pathom-aree, Wasu; Pumas, Chayakorn (Frontiers in Microbiology, 2021)
Thailand is an agricultural country. However, agricultural productivity relies on the heavy use of herbicides, especially paraquat. Paraquat accumulation is emerging as a problem in an ever-growing portion of agricultural land. Paraquat residues are toxic to plants, animals and aquatic organisms in the environment. Biological remediation is a process that can mitigate agricultural chemical contaminants. One of the interesting bio-remediators is bacteria. Certain soil bacteria not only remediate paraquat but some of them also possess plant-growth promoting properties, which provide advantages in field application. Thus, this study aimed to screen soil bacteria that could degrade paraquat and, at the same time, promote plant growth. Bacteria were isolated from paraquat-treated agricultural soil in Muang Kaen Pattana municipality, Chiang Mai province, Thailand. On the basis of morphological and 16S rDNA sequence analysis, the selected bacterium was identified as Bacillus aryabhattai strain MoB09. It is capable of growing in nitrogen-free medium. B. aryabhattai growth and paraquat degradation were found to be optimum at pH 7 and 30 °C. This selected strain also possessed plant-growth-promoting abilities, including indole production siderophore production phosphate solubilization and 1-aminocyclopropane-1-carboxylic acid deaminase activity. Paraquat degradation was also evaluated in pot experiment of cowpea (Vigna unguiculata). It was found that this strain could remediate the paraquat residue both in sterilized and non-sterilized soils. The cowpea plants grown in paraquat-contaminated soil with B. aryabhattai showed longer root and shoot length than those grown in soil without bacterial inoculation. In addition, B. aryabhattai also promoted the growth of cowpea under induced drought stress. These results suggested that B. aryabhattai could be applied to mitigate paraquat residue in soil and also to promote plant productivity for the organic crop production.